Ultra-soft wires for direct soldering on finger grids of solar cells. (September 2017) - Rendler, Li C.; Walter, Johann; Kraft, Achim; Ebert, Christian; Wiese, Steffen; Eitner, Ulrich
Abstract: We propose an interconnection concept for solar cells that enables the soldering of solder coated copper wires directly on the contact fingers of the front side metallization without the need of busbars or contact pads. By reshaping the copper wires we realize a wave-shaped stress relief structure. This reduces the yield force, the force value where plastic deformation of the wire starts, up to 90 % compared to straight wires and therefore minimizes mechanical stresses in the joint after the soldering process essentially. Our experimental analysis demonstrates the mechanical long-term stability of the interconnection (ΔP < 2 % after TC 370). The method enables a significant silver reduction by omitting solder pads or busbars on the front side and is especially suitable for the interconnection of exceptionally thin, stress sensitive solar cells or back contact solar cells with a minimized cell bow.